The Aggrieved Party of a Contractual Breach: Its Position, Rights and Duties, Limits of Sacrifices Under Hungarian and Comparative Law Instruments - Molnár, Andrea (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
A diligent and vigorous obligee may prepare for the performance or for the breach of a contract by its co-contractant, by applying measures appropriate to the circumstances, beginning from the precontractual phase, through complete or partial performance, or an accidental breach, right until the dissolution of the contractual relationship. The objectives of the entitled party are to foster performance or to find the less harmful outcome if a breach occurs. These objectives are promoted by the general principles of proportionality, the equilibrium and safety of obligations, and good faith. The aggrieved party has rights but obligations as well, not only to provide services but also to respect and protect the infringing party’s interests. With allowances and sacrifices, if necessary. What are the rights and obligations of an aggrieved party, what kind of conduct to carry out, and what assistance is provided by Hungarian and comparative legal instruments such as the Civil Code, the CISG and the UPICC? These questions are subjected to examination in the paper.